Successfully treated severe obstetric sepsis and acute respiratory distress syndrome with extracorporeal membrane oxygenation. (May 2016) - Benetis, Rimantas; Nadisauskiene, Ruta; Sirvinskas, Edmundas; Lenkutis, Tadas; Siudikas, Adakrius; Kadusauskaitė, Vytaute; Railaitė, Dalia; Sukovas, Arturas; Abraitis, Vytautas
We report a unique clinical case about an 18-year-old woman, immediately post-partum after an urgent C-section, who survived severe sepsis, acute respiratory distress syndrome (ARDS) and disseminated intravascular coagulation (DIC) and was successfully treated with 11 different antibiotics, massive blood transfusions and repetitive surgeries and was on extracorporeal membrane oxygenation (ECMO) support for 22 days. Although, ECMO is a time-limited procedure and most manufacturers do not advise more than 14 days of use, 1 the situation for this patient was life-threatening and ECMO, despite the dangerous risks listed above, was the only way to win time for the lungs to recover and for treatment of the underlying disease, while maintaining adequate oxygenation and circulation. Fortunately, the condition of this woman was stabilized and she achieved complete physical recovery, despite minor neurological deficit in the fingers of her right hand.